Cultural heritage of ancestral knowledge in health through midwives in Colombia. Ruling T-128 of 2022 of the Constitutional Court of Colombia - John Fernando Restrepo Tamayo; Elkin Centeno Cardona; Juliana Sinisterra Quintero (Postulados: Revista Sociojurídica)
Through Sentence T-128 of 2022, the Constitutional Court repairs the violation of the fundamental rights to the prot ection of the ethnic and cultural diver sity of the Nation, to wor k, to the vital minimum and to heal th in favor of sever al Afro-Colombian or ganizations of midwives, whose damage had been carried out through the Resolutions that the Ministry of Heal th which declared the heal th emer gency and established the administrative and economic contributions in favor of heal th personnel. The study of the judgment allows us to identify a sociological and legal line of ar gument wher e the legal assumptions ar e expressed in ter ms of facts, values and nor ms through which the recognition of midwives as a cultural her itage of ancestral knowledge in heal th is established